Pengaruh Penerapan E-Learning Terhadap Hasil Belajar Mahasiswa Informatika Universitas Dehasen Bengkulu - sa, Hermawan (JURNAL PETIK, 2021)
Abstract - This research aims to determine the effect of e-learning on student learning outcomes in the Introduction to Information Technology (PTI) course in the Informatics Study Program, Faculty of Computer Science, Dehasen University Bengkulu. This research is a quasi experimental study in the form of pretest and posttest. The population was 60 students as a sample. Data obtained by documentation techniques and knowledge tests. The documentation technique is used  to obtain data and information in the form of the number and student learning outcomes, while the knowledge test is given at the beginning (pre-test) and at the end (post-test) of the meeting. The collected data were analyzed using descriptive statistics. The analysis showed that the average student learning outcomes for the experimental class pre-test were 77.87, with a standard deviation of 7.18. The average pre-test student learning outcomes for the control class were obtained 74.27 with a standard deviation of 7.02. While the post-test average student learning outcomes in the experimental class obtained 84.67 with a standard deviation of 7.51 and the average student learning outcomes for the control class were 80.93 with a standard deviation of 5.43. There is a significant difference in student learning outcomes in the introductory information technology course between groups treated using conventional methods and groups treated using E-Learning in the Informatics study program, Faculty of Computer Science, Dehasen University, Bengkulu. Keywords,: E-Learning Effect,Learning outcomes  Abstrak - Penelitian ini bertujuan untuk mengetahui pengaruh e-learning terhadap hasil belajar mahasiswa pada mata kuliah Pengantar Teknologi Informasi (PTI) Program Studi Informatika Fakultas Ilmu Komputer Universitas Dehasen Bengkulu. Penelitian ini merupakan penelitian quasi experiment dalam bentuk Pretest dan posttest. Populasi berjumlah 60 orang mahasiswa sebagai sampel. Data diperoleh dengan teknik dokumentasi dan tes pengetahuan. Teknik dokumentasi digunakan untuk memperoleh data dan informasi berupa jumlah dan hasil belajar mahasiswa, sedangkan tes pengetahuan diberikan pada awal (pree tes) dan akhir (post tes) pertemuan. Data yang terkumpul dianalisis dengan menggunakan statistik deskriptif. hasil analisis menunjukkan bahwa rata-rata hasil belajar mahasiswa untuk pre-test kelas eksperimen sebesar 77,87, dengan standar deviasi 7,18. Rata-rata hasil belajar mahasiswa pree-tes untuk kelas kontrol diperoleh 74,27dengan standar deviasi 7,02. Sedangkan post-tes rata-rata hasil belajar mahasiswa kelas eksperimen diperoleh 84, 67 dengan standar deviasi 7,51 dan rata-rata hasil belajar mahasiswa kelas kontrol diperoleh 80,93 dengan standar deviasi 5,43. Terdapat perbedaan yang signifikan hasil belajar mahasiswa pada mata kuliah pengantar teknologi informasi antara kelompok yang diberi perlakuan menggunakan metode konvensional dengan kelompok yang diberi perlakuan dengan menggunakan E-Learning pada program studi Informatika Fakultas Ilmu Komputer Universitas Dehasen Bengkulu. Kata Kunci,: Pengaruh E-Learning, Hasil Belajar